ANALISA SEMIOTIKA KEKERASAN RASISME DALAM FILM DETROIT - Suryadi, Kurnia Wahyu (JURNAL KOMUNITAS, 2022)
The study aims to classify the types of racist violence and explain the meaning of racist violence in the Detroit film. This research used a qualitative method. The data collection method used observation and documentation techniques. This research implemented analysis from Roland Barthes, and it is used to analyze scenes in the Detroit film that contain elements of violent racism as the research data. The data are the dialogue of characters and also scenes in the Detroit film. The data will include three stages of semiotic analysis according to Roland Barthes semiotics analysis, namely, denotation, connotation, and myth. The first stage or denotation describes the real form of a sign, and the second stage or connotation is to interpret the meaning of a sign. Besides, this research data will also be analyzed based on the meaning of myth through the signs that contain elements of violent racism from the perspective of community culture. There are six categories of racist violence in the Detroit film: fascist and psychological violence, positive and negative influences, with or without object, with or without subject, intentional or not, visible and hidden. Based on six categories, there are five meanings, namely: injustice, disappointment, prejudice, intimidation, discrimination. Based on the five meanings in the scene, the dominant is intimidation.